The safety evaluation of ethanol extract of torbangun leaves (Coleus amboinicus Lour.) on mouse fetal development - Alfiah, Elma; Damanik, Muhammad Rizal Martua; Roosita, Katrin; Fahrudin, Mokhamad (Jurnal Gizi dan Pangan, 2018)
The purpose of this study was to evaluate the safety of ethanol extract from torbangun leaves on mouse fetal development. This research used 24 female pregnant mouse. The leaves extract was administered orally at dose level of 0; 0.56; 1.68 and 3.36 g/kg body weight. The extract was given from the first day until the eighteenth day of pregnancy period. The ethanol extract of Torbangun leaves contains flavonoids, saponins, tannins, and steroids. The result showed that consumption of 3.36 g/kg torbangun leaves extract had led to significant differences in the decrease of maternal weight change, number of live fetuses, fetal weight, and fetal length. Consumption of Torbangun leaves extract during pregnancy should be avoided due to its potency to interfere the fetal development.